2018
DOI: 10.3389/fmicb.2018.00972
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Metabolism of Fossil Hydrocarbons and Sulfide Minerals by the Lithobiontic Microbial Community Inhabiting Deep Subterrestrial Kupferschiefer Black Shale

Abstract: Black shales are one of the largest reservoirs of fossil organic carbon and inorganic reduced sulfur on Earth. It is assumed that microorganisms play an important role in the transformations of these sedimentary rocks and contribute to the return of organic carbon and inorganic sulfur to the global geochemical cycles. An outcrop of deep subterrestrial ~256-million-year-old Kupferschiefer black shale was studied to define the metabolic processes of the deep biosphere important in transformations of organic carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The relatives of Sulfuricella and Sulfuritalea have also been detected based on detection of sequences related to other genes of these genera (Watanabe et al, 2013; Kojima et al, 2014; Herrmann et al, 2015, 2017; Lau et al, 2016; Kumar et al, 2017, 2018; Feng et al, 2018; Luo et al, 2018). This is also the case for the other genome-sequenced species of Sulfurifustis and Sulfuricaulis (Watanabe et al, 2016a; Herrmann et al, 2017; Kumar et al, 2018; Włodarczyk et al, 2018). Furthermore, detailed inspections of the genomes of Sulfuricella and Sulfuritalea revealed the presence of characteristic genes for arsenic metabolism, arxAB and arrAB (Watanabe et al, 2014, 2017).…”
Section: Introductionmentioning
confidence: 62%
“…The relatives of Sulfuricella and Sulfuritalea have also been detected based on detection of sequences related to other genes of these genera (Watanabe et al, 2013; Kojima et al, 2014; Herrmann et al, 2015, 2017; Lau et al, 2016; Kumar et al, 2017, 2018; Feng et al, 2018; Luo et al, 2018). This is also the case for the other genome-sequenced species of Sulfurifustis and Sulfuricaulis (Watanabe et al, 2016a; Herrmann et al, 2017; Kumar et al, 2018; Włodarczyk et al, 2018). Furthermore, detailed inspections of the genomes of Sulfuricella and Sulfuritalea revealed the presence of characteristic genes for arsenic metabolism, arxAB and arrAB (Watanabe et al, 2014, 2017).…”
Section: Introductionmentioning
confidence: 62%
“…Jiang et al 2015) or in culture-independent analyses (e.g. Włodarczyk et al 2018). Furthermore, most of these genera are well-known rock weathering organisms such as Arthrobacter (Frey et al 2010),…”
Section: Discussionmentioning
confidence: 99%
“…C, Fe and S) and soil formation (Uroz et al 2009;Brantley et al 2012). The role of microbes in the weathering of shale has been extensively studied in natural environments (Petsch et al 2001;Petsch et al 2005;Joeckel et al 2005;Cockell et al 2011;Yesavage et al 2012;Zhu and Reinfelder, 2012;Li et al 2014;Włodarczyk et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that this shale rock contains nickel and vanadium porphyrins ( Tokarska, 1971 ; Sawłowicz, 1985 ; Szubert et al, 2006 ). So far, we have shown that the community of microorganisms inhabiting the shale rocks were responsible for the oxidation and dehydrogenation of kerogen and for the mobilization of fossil organic carbon in the oxidized form ( Stasiuk et al, 2017 ; Włodarczyk et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first sample (SR) was shale rock taken from a freshly exposed rock profile in which microorganisms were not detected ( Stasiuk et al, 2017 ). The second sample was a bacteria-inhabited shale rock (BISR) collected from the profile created 12 years ago ( Włodarczyk et al, 2018 ). In the second part of our study, SR was exposed to the bacterium Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%